Host immune genetic variations influence the risk of developing acute myeloid leukaemia: results from the NuCLEAR consortium - Sánchez-Maldonado, J M; Campa, D; Springer, J; Badiola, J; Niazi, Y; Moñiz-Díez, A; Hernández-Mohedo, F; González-Sierra, P; Ter Horst, R; Macauda, A; Brezina, S; Cunha, C; et al. (Blood cancer journal, 2020)
The purpose of this study was to conduct a two-stage case control association study including 654 acute myeloid leukaemia (AML) patients and 3477 controls ascertained through the NuCLEAR consortium to evaluate the effect of 27 immune-related single nucleotide polymorphisms (SNPs) on AML risk. In a pooled analysis of cohort studies, we found that carriers of the IL13rs1295686A/A genotype had an increased risk of AML (PCorr = 0.0144) whereas carriers of the VEGFArs25648T allele had a decreased risk of developing the disease (PCorr = 0.00086). In addition, we found an association of the IL8rs2227307 SNP with a decreased risk of developing AML that remained marginally significant after multiple testing (PCorr = 0.072). Functional experiments suggested that the effect of the IL13rs1295686 SNP on AML risk might be explained by its role in regulating IL1Ra secretion that modulates AML blast proliferation. Likewise, the protective effect of the IL8rs2227307 SNP might be mediated by TLR2-mediated immune responses that affect AML blast viability, proliferation and chemorresistance. Despite the potential interest of these results, additional functional studies are still warranted to unravel the mechanisms by which these variants modulate the risk of AML. These findings suggested that IL13, VEGFA and IL8 SNPs play a role in modulating AML risk.
Keywords: Male; lidé středního věku; náchylnost k nemoci; genotyp; nádorové biomarkery; Humans; Immunomodulation; Middle Aged; Biomarkers, Tumor; rizikové faktory; senioři; hodnocení rizik; frekvence genu; mužské pohlaví; Female; Leukemia, Myeloid, Acute; imunita; Aged; genetická variace; Immunity; ženské pohlaví; Polymorphism, Single Nucleotide; imunomodulace; alely; jednonukleotidový polymorfismus; akutní myeloidní leukemie; Genetic Predisposition to Disease; Adult; Gene Frequency; Steroids; genetická predispozice k nemoci; dospělí; lidé; steroidy; Disease Susceptibility; Genotype; Risk Assessment; Genetic Variation; Risk Factors; Alleles